Kinetic effect of a four-step and step-close approach in a volleyball spike jump for female athletes - Hsieh, C.; Cascarina, S.; Pingatore, J. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The purpose of the present study was to investigate the kinetic difference between two different volleyball spike jump techniques: a complete four-step approach and step-close approach. Five female collegiate volleyball players (age: 20.40 ± 1.85, height: 1.80 ± 0.02 m, body weight: 71.71 ± 4.18 kg) who play the middle hitter position were recruited. Each participant performed ten jumps for both four-step and step-close approaches and takeoff from two Kistler force platforms. Results indicated that there is no significant difference (P = .18) of vertical propulsive impulse between the two types of jump. The anterior-posterior (AP) net impulse of the four-step approach was significantly greater than a step-close approach (P < .01). Finally, the contact duration of propulsive phase for step-close technique is significantly greater than four-step approach technique (P < .05).